Will ‘Eco-Fashion’ Take Off? A Survey of Potential Customers of Organic Cotton Clothes in London (2019)
This paper shows the results of a research that defines potential customers for organic cotton clothing in London in relation to their organic produce consumption. The methodology employed a positivistic approach and a combination of exploratory and descriptive research. It included a qualitative exploratory phase of seven in-depth interviews and a quantitative conclusive descriptive phase of 100 face-to-face applied questionnaires.The study suggests that most responders present positive attitudes towards organic cotton fashion. There is no evidence among the responders of a direct relation between consuming organic produce and the willingness to purchase organic clothing. However, interviewees with a higher degree of organic food consumption do exhibit higher knowledge about organic clothing, higher aspirations to enhance their quality of life and a stronger desire for hazardous chemical residue-free materials; they, as well, place a lower importance on the organic clothing premium price. The interest in environmental protection is also a characteristic of these potential customers; nevertheless, it is not necessarily related to higher organic food intakes. As with organic food, motivations for buying organic clothing are mainly related to specific characteristics of the product that directly benefit the consumer. Results have to be interpreted in light of what other studies, such as that by Carrigan et al. (2001), have revealed regarding purchase behaviour, which often remains unaffected by ethical concerns even though consumers may express willingness to purchase ethically.This research can be useful for marketers who want to better understand consumers with higher willingness to buy organic clothing. No studies existed at the time of the study that related the value that consumers give to the attributes of organic cotton clothing and their organic food intake.